From overexcitabilities to openness: Informing gifted education with psychological science. Issue 1 (2nd January 2016) - Vuyk, M. Alexandra; Kerr, Barbara A.; Krieshok, Thomas S.
ABSTRACT: In the theory of positive disintegration (TPD), Dabrowski described overexcitabilities (OEs), manifestations of inner energy with a developmental purpose that appear more common in gifted individuals. Unfortunately, most studies present OEs outside of the context of the original theory as if they were standalone traits applicable to gifted students. In this atheoretical conceptualization, OEs seem to define the personality trait of openness to experience described in the five-factor model of personality (FFM) as each OE can be matched with a specific facet of openness. Descriptions of facets of openness and corresponding OEs are strongly similar. In this article we argue that they are conceptually equivalent and that current research on openness and OE supports this assertion. The FFM has robust empirical support, and TPD lacks empirical support; additionally, OEs as currently presented in gifted education deviate from TPD's original tenets. Therefore, gifted education should shift its way of explaining these tendencies by framing them as the personality trait of openness to experience rather than OEs.